PHARMACOGNOSTICAL STANDARDISATION OF TYPHONIUM ROXBURGHII SCHOTT - Selvakumari, P. Annie Sulochana (Malaysian Journal of Science, 2016)
Typhonium roxburghii Schott of Araceae is a common medicinal plant. The corms possess rubifacient properties and they are used in diarrhea and for dermatitis. In South India, it occurs in Kerala and Karnataka. In Tamil Nadu, it is cultivated, and occurs as an escape. Pharmacognosy is an important link between pharmacology and medicinal chemistry. Pharmacognostical standards are prepared by systematic study of the drug. Morphological and anatomical descriptions of plants, pharmacognostical standards such as structural standards, analytical standards and physical constants were obtained by employing standard methods of analysis as described in Pharmacopoeia of India. The results of the present investigation provide dependable diagnostic features of the vegetative organs of the plant for the identity of the drug in entire and in fragmentary conditions. Keywords: Typhonium roxburghii, pharmacognosy, morphology, anatomy, physicochemical constants, phytochemistry